The problematics of accountability: Internal responses to external pressures in exposed organisations. (October 2019) - Yasmin, Sofia; Ghafran, Chaudhry
Abstract: This paper seeks to contribute to the emerging stream of literature on NGO accountability by drawing on the theoretical assertions of the problematics of accountability. It discusses how accountability has become problematic for NGOs by examining how these problems are created and how NGOs subsequently respond. Drawing on in-depth interview data complemented by extensive documentary analysis, we explore the accountability experiences of Muslim NGOs operating in the UK. We highlight how specific accountability regimes are influenced by the prevailing political, social and economic context within which they operate. We suggest this has caused Muslim NGOs to become 'exposed' organisations where demands for accountability, framed by security and counter-terror concerns, are limiting their ability to be accountable. Utilising insight from Kearns (1994) we explain how Muslim NGOs respond to these problems. We find engagement with discretionary accountability tactics allow the NGOs to gain trust of stakeholders, whilst strategic change processes help the NGOs to anticipate and negotiate heightened accountability demands. We discuss the implications of our findings for both theory and practice.